The Effect of Combination Therapy of Brain Gymnastics and Elderly Gymnastics on Improving Cognitive Function in the Elderly - Amanah, Hanni’ Ma’rifatul; Hikmawati, Isna; Asiandi, Asiandi; Riyaningrum, Wahyu (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Semarang, 2024)
Background: The increasing prevalence of elderly individuals experiencing a decline in cognitive function impacts their daily activities and increases their dependency on others. The study aimed to determine the effect of combined brain exercise and elderly exercise therapy on improving cognitive function in older people at Sudagaran Banyumas Social Service Home for the Elderly. Method: This quantitative study utilized a Quasi-Experimental design with a pretest-posttest control group approach. The sample consisted of 30 elderly individuals, selected using total sampling techniques. The instrument used was the Mini-Mental State Examination (MMSE). Data analysis was conducted using the Mann-Whitney test. Result: The results revealed that most respondents were female, with 11 women (73.3%) in the intervention group and eight women (53.3%) in the control group. The average age of respondents was between 60-69 years, with ten individuals (66.7%) in the intervention group and six individuals (40.0%) in the control group. Most respondents were in elementary school education, with seven individuals (46.7%) in the intervention group and six individuals (40.0%) in the control group having no formal education. The MMSE scores of older people who received the intervention revealed a significant increase, from an average score of 18.67 to 20.73. Conclusion: Indicating a substantial effect of combined brain exercise and elderly exercise therapy on improving cognitive function in older people. Older people are expected to regularly engage in activities to enhance cognitive function further